How do secondary schools in Hong Kong manage diversity in age, gender, and culture; and the implications. - Ip, Chun Him (2016)
The problem I am trying to solve in this paper is how do secondary schools in Hong Kong manage diversity in age, gender, culture; and the implications. The approach I adopt to solve the problem is a qualitative research method with semi-structured interview as a primary data collection method. This article gives an overview of the discrimination situation in Hong Kong. Specific terms are defined under the literature review. This paper touches upon 3 approaches to diversity, 4 benefit of managing diversity, and 5 practices to manage diversity. The results obtained in the literature review include the under representation of women in senior position, gender discrimination in recruitment, and age discrimination towards older workers. This article compares the interview finding with respond to data obtained in the literature review, and summarizes key findings.